[Medical Essays] : [1891-1897] - Martin, Christopher (editorial no identificada)
Compilación creada de forma independiente de diversos artículos médicos del cirujano Christopher Martin, del Birmingham and Midland Hospital for Women. Incluye los siguientes ensayos: “Urethral Caruncle”, “Six Cases of Uterine Myoma, Illustrating Various Methods of Removal of the Tumor”, “The Nerve Theory of Menstruation”, “The After-Treatment of Cases of Abdominal Section”, “Fainful Menstruation”, “The Struggle for the Life of Others”, “When and How to Curette the Uterus”, “On Pan-Hysterectomy, or Total Extirpation of the Uterus by Abdominal Section”, y “A Case of Rupture of the Liver Successfully Treated by Abdominal Section”.